Potential Radiological Hazard of Coal-Fired Power Plant - Oktamuliani, Sri; Caredek, Puspa Tirta; Wiyono, Muji; Wahyudi, Wahyudi; Kusdiana, Kusdiana (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
Coal-fired power plants not only generate electricity but also produce coal ash containing naturally occurring radionuclides, which may pose radiological hazards to workers and nearby residents. This study aimed to assess the radiological risks associated with natural radionuclides present in coal ash and surrounding soil near PT Sugar Labinta, Lampung. To achieve this, samples of fly ash, bottom ash, and soil were systematically collected, and the specific activities of radionuclides radium-226, thorium-232, and potassium-40 were measured using gamma-ray spectrometry with High-Purity Germanium (HPGe) detectors. These measurements served as the basis for evaluating potential radiation hazards. The results showed that the gamma index values for fly ash (zero point seven seven seven), bottom ash (zero point three seven zero), and soil (zero point five one four) were all below the safety threshold (gamma index less than or equal to one), indicating low levels of gamma radiation and minimal radiological risk. Similarly, the external hazard index values ranged from zero point one two six to zero point six zero five, remaining under the recommended limit (external hazard index less than or equal to one). However, several samples, particularly fly ash (up to ninety-nine point zero two five nanogray per hour) and soil (up to sixty-five point five one one nanogray per hour), had absorbed dose rates exceeding the global average set by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). While most soil samples had annual effective dose equivalents below the standard limit of zero point zero seven millisievert per year, fly ash exceeded this value, signaling the need for continued monitoring, especially in residential areas near the power plant chimney. These findings suggest that coal ash and soil around PT Sugar Labinta generally present a low radiological risk. However, ongoing monitoring is essential to detect and mitigate potential long-term exposures. The study contributes valuable data for environmental radiation assessments and supports the implementation of effective radiological protection strategies in coal-fired power plant areas.